The Effect of Successor Readiness on Family Business Sustainability - Silvia Fajari Rasyieda; Seni Pitriani; Mira Nurfitriya; Azizah Fauziyah (Proceedings Series on Social Sciences & Humanities, 2024)
Leadership succession in a family business is the process of transferring leadership from predecessor to business successor, this process involves preparing a successor who will take over leadership and be responsible for the family business. Ineffective succession planning will not be able to make a successor in accordance with company goals that will cause the company to fall. This study aims to determine the effect of successor readiness on the sustainability of family business. With the object of research of students of the Indonesian University of Education, Tasikmalaya Campus. This study used quantitative methods, with a descriptive approach and journal analysis related to sustainability factors in family businesses. Based on the results of the study, there are allegations that successor readiness has a positive effect on the sustainability of family businesses and provides useful insights on how families can improve family business sustainability through successor readiness.